Evaluating Different Techniques Of Laparotomy Closure: A Prospective Study - Donda, Jaykumar; Pradhan, Krunal; E. Shah, Riddhi (Journal of Neonatal Surgery, 2025)
Background: Optimal laparotomy closure techniques remain a subject of debate despite advances in surgical methods and materials. Patients currently experience a variety of surgical complications including wound dehiscence and surgical site infections (SSIs) and incisional hernias and postoperative pain that persists. Identifying the most effective closure technique could reduce the incidence of these complications, minimize reoperations, and improve patient outcomes. Methods: A 12-month prospective research was carried out at a tertiary care hospital.. A total of 150 patients requiring midline laparotomy were consecutively recruited and randomized into three groups (n=50 per group): Group A utilized interrupted, conventional sutures; Group B employed continuous, slowly absorbable sutures; and Group C applied a layered closure technique combining interrupted fascia sutures with continuous skin sutures. Wound complication rates including infections and incision dehiscence and incisional hernia served as the main study outcome measure during six months of follow-up. Secondary outcomes included operative time for closure, postoperative pain scores, and patient quality-of-life indices. Data were analyzed using appropriate univariate and multivariate statistical tools. Results: The participants demonstrated equivalent characteristics when researchers evaluated each group at the start of the study. Research data showed that Group C patients recorded lower amounts of wound complications when compared to Groups A and B with statistical significance (p<0.05). The surgical conclusion time was considerably shorter in Group B (p<0.01) yet postoperative discomfort reached its minimum level in Group C. At six months the patients in Groups B and C developed few incisional hernia cases with Group C achieving statistical significance (p<0.05). Conclusion: A layered closure technique combining interrupted fascial sutures with continuous cutaneous suturing appears to offer a balanced approach, yielding fewer wound complications and acceptable operative times. These findings underscore the importance of appropriate suture selection and closure technique to optimize outcomes